Pro-regenerative Dialogue Between Macrophages and Mesenchymal Stem/Stromal Cells in Osteoarthritis - Bohaud, Candice; Contreras-Lopez, Rafael; De La Cruz, Jholy; Terraza-Aguirre, Claudia; Wei, Mingxing; Djouad, Farida; Jorgensen, Christian (Frontiers in Cell and Developmental Biology, 2021)
Osteoarthritis (OA), the most common degenerative and inflammatory joint disorder, is multifaceted. Indeed, OA characteristics include cartilage degradation, osteophytes formation, subchondral bone changes, and synovium inflammation. The difficulty in discovering new efficient treatments for OA patients up to now comes from the adoption of monotherapy approaches targeting either joint tissue repair/catabolism or inflammation to address the diverse components of OA. When satisfactory, these approaches only provide short-term beneficial effects since they only result in the repair and not the full structural and functional reconstitution of the damaged tissues. In the present review, we will briefly discuss the current therapeutic approaches used to repair the damaged OA cartilage. We will highlight the results obtained with cell-based products in clinical trials and demonstrate how the current strategies result in articular cartilage repair showing restricted early-stage clinical improvements. And in order to identify novel therapeutic targets and provide to OA patients long-term clinical benefits herein we will review the basis of the regenerative process. We will focus on macrophages and their ambivalent roles in OA development and tissue regeneration and review the therapeutic strategies to target the macrophage response and favor regeneration in OA.